1994
DOI: 10.3354/meps115283
|View full text |Cite
|
Sign up to set email alerts
|

Size distribution of chlorophyll a biomass and primary production in a temperate estuary (Southampton Water): the contribution of photosynthetic picoplankton

Abstract: Size-fractionated chlorophyll a (chl a) biomass and primary production rate (>3 pm, 1-3 pm and < l pm) and picophytoplankton abundance (both prokaryotic and eukaryotic) were investigated in Southampton Water (south coast of England), with routine sampling at 2 stations, representative of conditions in the mid and outer estuary. In the mid estuary the cycle of chl a biomass in the >3 pm size fraction was characterized by a small spring peak and a more intense summer peak. In the outer estuary a chl a maximum in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 39 publications
7
44
1
1
Order By: Relevance
“…Furthermore, during fall and winter, the chl a-specific photosynthetic rate for the small size fraction (<5 μm) is higher than the large size fraction (>5 μm) at all stations. The same results were obtained in other coastal and oceanic waters (Howard and Joint 1989;Iriarte and Purdie 1994). This was likely due to the physiological advantages of a higher efficiency of photon absorption and nutrient uptake for the small-sized phytoplankton under low light and nutrient conditions (Raven 1986).…”
Section: Dominance Of Large Diatoms In Hong Kong Waterssupporting
confidence: 72%
“…Furthermore, during fall and winter, the chl a-specific photosynthetic rate for the small size fraction (<5 μm) is higher than the large size fraction (>5 μm) at all stations. The same results were obtained in other coastal and oceanic waters (Howard and Joint 1989;Iriarte and Purdie 1994). This was likely due to the physiological advantages of a higher efficiency of photon absorption and nutrient uptake for the small-sized phytoplankton under low light and nutrient conditions (Raven 1986).…”
Section: Dominance Of Large Diatoms In Hong Kong Waterssupporting
confidence: 72%
“…In most systems, after the winter or spring bloom (usually consisting of large diatom cells) collapses, smaller cells (pico-and nanoplankton) tend to dominate (Nielsen & Richardson 1989, Andersson & Rudehall 1993, Iriarte & Purdie 1994, Rodriguez & Guerrero 1994, Brussaard et al 1995, Malej et al 1995. Such a shift, with the potential subsequent development of the microbial loop, seems to be the routine source of fixed carbon to pelagic food webs, if we accept that net phytoplankton blooms (i.e.…”
Section: Excludingmentioning
confidence: 99%
“…Additionally, mesozooplankton directly interact with the microbial loop food web by grazing upon heterotrophic protists, especially when small phytoplankton dominate the autotrophic community or under oligotrophic conditions . Summer nutrient depletion, which is also considered as evidence for the dominance of pico-and nanoplanktonic organisms (Anderson & Rudehall 1993, Iriarte & Purdie 1994, Malej et al 1995, has been observed in Maliakos Gulf (Kormas et al unpubl.). According to Krupatkina (1990), oligotrophic waters seem to be a most favourable environment for smaller organisms due to more efficient utilisation of near to analytical zero concentration of nutrients, higher photosynthetic activity and practically zero sinking rate.…”
Section: Excludingmentioning
confidence: 99%
“…In oligotrophic oceans, Synechococcus spp. contribute up to > 50% of the total photosynthetic carbon fixation (Iriarte and Purdie 1994). Furthermore, during warm seasons, Synechococcus spp.…”
Section: Introductionmentioning
confidence: 99%